2019
DOI: 10.21873/invivo.11790
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Radiation Dermatitis Using a Film-forming Silicone Gel During Breast Radiotherapy: A Pilot Randomized-controlled Trial

Abstract: Background/Aim: To evaluate whether topical use of a film-forming silicone gel (StrataXRT ®) could reduce radiation dermatitis compared to a moisturizing cream (Xderm ®) in patients receiving whole breast radiotherapy. Patients and Methods: A total of 56 patients with breast cancer were randomized to use StrataXRT or X-derm. The severity of radiation dermatitis was graded using physiological skin parameters, clinician-assessed visual rating scales and patient-reported symptoms. Changes in these parameters from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…As such, RID can be caused by a variety of factors and accounts for a high proportion of the adverse effects of conventional therapies in breast cancer patients, but there is currently no standard management or guideline for RID prevention (Wong et al, 2013;Chan et al, 2014). However, in clinical practice, topical managements, including moisturizing cream, are generally applied to patients with RID and their comparative studies have also been researched (Haruna et al, 2017;Ahn et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As such, RID can be caused by a variety of factors and accounts for a high proportion of the adverse effects of conventional therapies in breast cancer patients, but there is currently no standard management or guideline for RID prevention (Wong et al, 2013;Chan et al, 2014). However, in clinical practice, topical managements, including moisturizing cream, are generally applied to patients with RID and their comparative studies have also been researched (Haruna et al, 2017;Ahn et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…When applied topically, StrataXRT dries to form a thin, flexible, protective layer that is gas permeable and waterproof. This environment leads to rapid wound healing and faster skin recovery [39]. In a relatively large single-blind randomized controlled trial by Chan et al, a reduced risk of developing ARD was obtained with prophylactic application of StrataXRT dressings [40].…”
Section: Gel Dressingsmentioning
confidence: 99%
“…Two other studies verifying the prophylactic use of StrataXRT confirmed these findings. An RCT involving 56 patients treated for breast cancer demonstrated a reduction in objectively measured ARD severity in the StrataXRT group [39]. The other study proved StrataXRT's noninferiority to Mepitel film in ARD prevention [41].…”
Section: Gel Dressingsmentioning
confidence: 99%
“…This range of values should be considered in studies of hypofractionated breast radiation, including H-SIB. In this context, there is also interest in radiation techniques that facilitate steep dose gradients between the boost PTV and whole breast PTV or between the whole breast PTV and surrounding normal tissue, where excessively high maximum doses should be avoided to minimise the probability of radiation-induced side effects (21)(22)(23).…”
mentioning
confidence: 99%
“…The technical details of helical tomotherapy have been described previously (22). Briefly, a tomotherapy unit is a hybrid comprising a 6-MV linear accelerator and a helical CT scanner.…”
mentioning
confidence: 99%